Programiranje z modulo-2 - Brodnik, Andrej (Informatica (Ljubljana), 1987)
In this paper is a description of the Modula-2 programming language. The description is divided into two parts. In the first part, we discuss the essential data, control, and programming structures of the language which separate Modula-2 from other modern languages, concluding wise the notation of a module and modular programming, and some principles of system or low-level programming. In the second part of this contribution, Modula-2 is compared to other three modern programming languages: Pascal, Ada and C.
Keywords: computer science; modula-2; programming languages; programski jeziki; računalništvo